Heat‐ or Water‐Driven Malleability in a Highly Recyclable Covalent Network Polymer. (27th March 2014) - Taynton, Philip; Yu, Kai; Shoemaker, Richard K.; Jin, Yinghua; Qi, H. Jerry; Zhang, Wei
<x xml:space="preserve">Abstract</x> A catalyst‐free malleable network polymer that can be reprocessed by application of either water or heat is prepared through imine chemistry. This material is recycled from a fine powder to a coherent solid with >100% recycling efficiency through several generations. It is also reprocessed at ambient temperature using only water, thus potentially leading to energy‐neutral green processing of the material. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>